2016
DOI: 10.1080/14693062.2016.1169392
|View full text |Cite
|
Sign up to set email alerts
|

REDD+, transformational change and the promise of performance-based payments: a qualitative comparative analysis

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 19 publications
0
49
0
6
Order By: Relevance
“…Savedoff (2016) argues that a cash-on-delivery model 7 for REDD+ could increase cost efficiency, be more effective, and improve governance as recipient governments would realign behavior to achieve results -if the targeted outcomes are well-defined, agreed upon and adequately rewarded. Findings from a comparative policy study in 13 countries showed that the three countries with access to performance-based finance for REDD+ (combined with national ownership over the REDD+ process) tended to advance relatively more quickly in implementing policy reforms than the others (Brockhaus et al 2016). However, the same study also found that overall progress with REDD+ was very slow, a tedious, sticky process.…”
Section: Timing and Sequencing Of Paymentsmentioning
confidence: 78%
See 2 more Smart Citations
“…Savedoff (2016) argues that a cash-on-delivery model 7 for REDD+ could increase cost efficiency, be more effective, and improve governance as recipient governments would realign behavior to achieve results -if the targeted outcomes are well-defined, agreed upon and adequately rewarded. Findings from a comparative policy study in 13 countries showed that the three countries with access to performance-based finance for REDD+ (combined with national ownership over the REDD+ process) tended to advance relatively more quickly in implementing policy reforms than the others (Brockhaus et al 2016). However, the same study also found that overall progress with REDD+ was very slow, a tedious, sticky process.…”
Section: Timing and Sequencing Of Paymentsmentioning
confidence: 78%
“…Achieving reduced emission results is influenced by a complex and varied set of political, socioeconomic and environmental factors (e.g. El Niño-induced forest fires) including institutional bureaucracies, enabling conditions and opportunity costs (Angelsen 2013;Brockhaus et al 2016). If countries are to bear the costs of implementing policy reforms, they may be unwilling to participate in REDD+ because of these in part, noncontrollable, risks (Clist and Dercon 2014).…”
Section: Key Issues When Designing Adequate Predictable and Effectivmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that Brazil has strong ownership over REDD+ policy processes, as most relevant actors are domestic rather than international, contrasting with other country contexts (see ). This is a positive sign for REDD+ progress, since national ownership is necessary for success (Davis 2010;Di Gregorio et al 2012b;Korhonen-Kurki et al 2014;Brockhaus et al 2016). Despite national ownership, it is evident that the media coverage of this debate is strongly keyed to the international policy process at the COPs as in other REDD+ countries (Cronin et al 2016;Khatri et al 2016;Vijge et al 2016).…”
Section: Pdf Editormentioning
confidence: 99%
“…Although all the countries have developed REDD+ strategies and are in the process of developing reference emission levels and safeguards, which are the other three elements of REDD+ (UNFCCC, 2010), the REDD+ literature (e.g. Angelsen et al, 2012;Brockhaus et al, 2016;Minang et al, 2014) shows that none of the studied countries has addressed the drivers of deforestation and forest degradation that should be the main focus of REDD+.…”
Section: Discussionmentioning
confidence: 99%